Occurrence of suicide and seasonal variation Ocorrência de suicídio e variação sazonal - Pedro Retamal C.; Derek Humphreys (Universidade de São Paulo, 1998)
OBJECTIVE: To review the estimated suicide rates for the Region Metropolitan, the main socio-political center in Chile, for the period 1979-1994, and to determine whether they follow a seasonal pattern. METHOD: Data available for the period 1979-94 at the Forensic Services in Chile was analyzed using ANOVA. RESULTS: It was register 5.386 suicides. While the "warm" months (October, November, December & January) concentrated 39.0% of cases, the so called "cold" months reported 28,7%. This contrast is made even clearer by the month-to-month analysis, showing the highest suicide rate in December (10.9%) against the lowest rate in June (7.0%). Further statistical analysis revealed these differences to be significant. CONCLUSION: The study shows that in Chile, representing as it does the Southern Hemisphere, the suicide rates tend to present a seasonal variation as has elsewhere been determined for in the North Hemisphere. OBJETIVO: Realizou-se revisão das taxas estimadas de suicídio na Região Metropolitana, setor sociopolítico principal do Chile, no período de 1979-94, para determinar se essas taxas seguem um padrão sazonal. MÉTODO: Os dados disponíveis para o período 1979-94 no Serviço Médico Legal foram analisados pela ANOVA. RESULTADOS: Foram registrados 5.386 suicídios, porém, nos meses "cálidos" (outubro, novembro, dezembro, janeiro) concentram-se os 39,0% dos casos. Nos meses frios foram consignados 28,7%. Esta observação fica mais clara pela análise mês a mês, demonstrando taxas mais altas em dezembro (10,0%) e mais baixas em junho (7%). Através de análises estatísticas ficou demonstrado que a diferença é significativa. CONCLUSÃO: Foi demonstrado que no Chile, sendo representativo do Hemisfério Sul, o índice de suicídio tem a tendência de apresentar uma variação sazonal, assim como tem sido demonstrado em numerosas publicações no Hemisfério Norte.